2017
DOI: 10.1519/jsc.0000000000001711
|View full text |Cite
|
Sign up to set email alerts
|

Allometric Grip Strength Norms for Children of Hawaiian Lineage

Abstract: The purpose of the study was to determine allometric exponents for scaling grip strength in children that effectively control for body mass (BM) and stature (Ht) and to develop normative grip strength data for Hawaiian children. One thousand, four hundred thirty-seven students (754 boys) from a rural community in Hawaii participated in this 5-year study, resulting in 2,567 data points. Handgrip strength, BM, and Ht were collected every year. Multiple log-linear regression was used to determine allometric expon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…The normative values for HS are consistent with the magnitude and direction related to sex and age previously reported in different studies around the world, 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 in which male children and adolescents had consistently higher scores than their female peers. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 It is also consistent with an increase in the HS value proportional to age in both males and females. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , ...…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The normative values for HS are consistent with the magnitude and direction related to sex and age previously reported in different studies around the world, 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 in which male children and adolescents had consistently higher scores than their female peers. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 It is also consistent with an increase in the HS value proportional to age in both males and females. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , ...…”
Section: Discussionsupporting
confidence: 90%
“… 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 It is also consistent with an increase in the HS value proportional to age in both males and females. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 …”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Both RH and LH players showed moderately significant bilateral differences in favor of the dominant hand. There are only few comparable studies in the sport literature (Table 5), more authors have analyzed handgrip strength and bilateral differences in 11-12-year-old children (Butterfield & Lehnhard, 2009;Fredriksen, Mamen, Hjelle, & Lindberg, 2018;Gómez-Campos et al, 2018;Hepping et al, 2015;Kocher et al, 2017;Omar, Alghadir, Zafar, & Al Baker, 2018;Ploegmakers, Hepping, Geertzen, Bulstra, & Stevens, 2013). While 43.03% of research participants were found to have bilateral differences >15%, 26.67% were found to have differences as high as >20%.…”
Section: Discussionmentioning
confidence: 99%